Development of Promoting Self-Discipline Model of Students in Banglane Wittaya School. - Kasemsuk, Sornchei; Untaweesin, Apinun; Intarak, Choomsak (Saengtham College Journal, 2023)
The purposes of this research and development were : 1) to study the problem of self-discipline among students at Banglane Wittaya School , 2) to design and create a model for enhancing self-discipline of students at Banglane Wittaya School, 3) to assess the consistency of the self-discipline enhancing model of students at Banglane Wittaya School, and 4) to study the effects of using a model for enhancing self-discipline among students in Banglane Wittaya School in in terms of efficiency, effectiveness, value and satisfaction. The sample group It was obtained from purposive sampling, consisting of 15 homeroom teachers and 54 students. The tools used were questionnaires, semi-structured interviews form, and the efficiency, effectiveness, value and satisfaction assessment form. The statistics used in the research were frequency, percentage, mean, standard deviation. and content analysis. The findings revealed that the overall of self-discipline problem of students of Banglane Wittaya School is at moderate level. The enhancing self-discipline model of students of Banglane Wittaya School comprised of four steps which are: (1) preparedness, (2) self-discipline enhancing plan, (3) action coordination, and (4) monitoring and evaluation . The content validity of the model was IOC value between 0.80 and 1.00, which means that it can be applied in the experiment. The effects of model in term efficiency, effectiveness, value and satisfaction were at high levels. The recommendation was that class teachers should implement this model as a guideline for self-discipline activities for better responsibility and punctuality of students